2014
DOI: 10.1080/13662716.2014.879252
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Capital in Lowering the Barriers to Engaging in Innovation: Evidence from the Spanish Innovation Survey

Abstract: This paper focuses on the role of human capital in reducing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 44 publications
(32 reference statements)
5
63
0
4
Order By: Relevance
“…Access to finance is very pronounced issue for firms engaged in innovation projects (D´Este, Rentocchini, & Vega-Jurado, 2014). They are highly pronounced in young, small and medium firms engaged in R&D activities (Segarra, García-Quevedo, & Teruel, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to finance is very pronounced issue for firms engaged in innovation projects (D´Este, Rentocchini, & Vega-Jurado, 2014). They are highly pronounced in young, small and medium firms engaged in R&D activities (Segarra, García-Quevedo, & Teruel, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, it is difficult to define an appropriate measure of many constraints and measure their presence with great precision. Therefore, studies often rely on perception (DʹEste et al, 2014;DʹEste et al, 2012;Galia & Legros, 2004;Mohnen & Röller, 2005;Tourigny & Le, 2004).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…One reason put forward by these works relates to the complexity of green technology given its early stage. Looking at the innovation barriers as well as failure in innovation activities faced by born green companies can inform both recent attempts in the innovation literature (Marin et al 2015;D'Este et al 2014) as well as the conundrum found by the papers in this special issue. Evidently, these studies contained here may have only scratched the surface of the problem and future work should try to dig deeper into this.…”
Section: Concluding Remarks and Potential Areas For Future Researchmentioning
confidence: 99%
“…Cooperation strategies that incorporate knowledge intensive business service firms (outsourcing) have a considerably greater impact on introducing innovation on the market [9]. Lack of qualified human capital is a barrier for starting innovation activities and is also a serious impediment to continuous innovator firms [10]. New management techniques are most common type of innovation in service companies in Spain [11].…”
Section: Current Literaturementioning
confidence: 99%